New Testament Apocrypha ; v. 2 - Hennecke, Edgar, 1865-1951; Schneemelcher, Wilhelm; Wilson, R. McL. (Philadelphia, PA Westminster, 1963)
Contents : v. 2 : Writings relating to the Apostles; Apocalypses and related subjects. Includes bibliographical references.
Keywords: Apocrypha, New Testament -- commentaries